Spatial Pattern Analysis of Agricultural Drought in the Jatiluhur Reservoir’s Irrigation Area Using Normalized Drought Index (NDDI) MODIS Satellite Image - Zubair, Ahmad; Sakina, N C; Khairunnisa, N; Siddiq, Ayyasy; Rustanto, Andry; Zulkarnain, Faris; Dimyati, Muhammad (UI Scholars Hub, 2024)
Agricultural drought occurs in various irrigation areas in Indonesia, one of which is the Jatiluhur Reservoir’s irrigation area. Agricultural drought in this area occurs due to several factors, including the natural phenomenon of climate anomalies which causes the length of the dry season, and also due to less optimal irrigation networks, damaged networks and other obstacles. But, not all agricultural land in the irrigated area experiences drought. Agricultural land affected by drought is important to know its spatial and temporal distribution to determine priority locations in drought disaster management, especially on agricultural land. Therefore, this study aims to examine the spatial pattern of agricultural drought in the irrigation area of the Jatiluhur Reservoir from 2000–2020. The index used in this study is the Normalized Difference Drought Index (NDDI). MODIS image version MOD13Q1 is used by dividing the dryness class into three classifications, namely dry (>0.5), rather dry (0-0.5), and normal (<0.5). The results showed that the most extensive drought in rice paddy fields occurred in 2015 with a dry index of 8574.19 Hectares. Meanwhile, agricultural drought in this area occurs on average from June to September, especially in the Jayalaksana Village and Setialaksana Village, Bungin Sub-District, Bekasi Regency. These two villages are affected by agricultural drought every single year. The spatial pattern of agricultural drought shows that it follows the pattern of the irrigation network. It is necessary to investigate the correlation between agricultural drought and irrigation network in the next research.